2016
DOI: 10.1364/josab.33.000c17
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of surface plasmon polariton dispersion in gold and silver thin films

Abstract: We image the dispersion of surface plasmon polaritons in gold and silver thin films of 30 nm and 50 nm thickness, using angle-resolved white light spectroscopy in the Kretschmann geometry. Calibrated dispersion curves are obtained over a wavelength range spanning from 550 nm to 900 nm. We obtain good qualitative agreement with calculated dispersion curves that take into account the thickness of the thin film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In turn, this tunability could be used to improve the performance of devices for a variety of applications, such as perfect absorbers, photovoltaics, hydrogen storage, metallurgy, catalysis, and electrocatalysis . However, in contrast to the well‐investigated dispersion relation of pure noble metals (Ag and Au), the dispersion of SPPs for Ag–Au alloys has rarely been explored . Additionally, the correlations between the effect of alloying on the optical dispersion relation, the threshold of the interband transition, and the new material's band structure are still not well understood.…”
mentioning
confidence: 99%
“…In turn, this tunability could be used to improve the performance of devices for a variety of applications, such as perfect absorbers, photovoltaics, hydrogen storage, metallurgy, catalysis, and electrocatalysis . However, in contrast to the well‐investigated dispersion relation of pure noble metals (Ag and Au), the dispersion of SPPs for Ag–Au alloys has rarely been explored . Additionally, the correlations between the effect of alloying on the optical dispersion relation, the threshold of the interband transition, and the new material's band structure are still not well understood.…”
mentioning
confidence: 99%
“…By this, we achieve two goals -first, as also used in Refs. [4][5][6][7][8], the sample is simultaneously probed by the many plane-waves making up the converging beam and having an angular span of 10 degrees (in air). Using Snell's law, this is translated to a range of incident angle of 41°-48° with respect to the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Taking advantage of the spatial-interrogation capabilities, we measured the SPP dispersion curves of metalstrip waveguides and demonstrated that our method allows local measurement of waveguides which are as narrow as 3 µm. Like previous Fourier-space imaging methods used for dispersion measurements [4][5][6][7][8][9], our method can be used for broadband, high-resolution and real-time sensing applications. However, in addition, it permits spatial discrimination of several microns and mapping of spatially-inhomogeneous structures, by lateral scanning over the interrogated area.…”
Section: Dispersion Of Plasmonic Waveguidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the presence of magnified-field environments, charge oscilltions at metals surfaces couple strongly with the EM field in its immediate dielectric vicinity, producing surface plasmon polaritons (SPP) which travel along the interface of metals and dielectrics. 136 Recent work has shown gold-film structures under optical illumination result in SPPs with evanescent field-scales of up to ~50 nm reach that can couple strongly with 2D quantum wells as far as 20 nms away, leading to either enhancement or drop in exciton radiation efficiency depending the coupling with the SPPs. 137 In our case, being atomically proximal to the MoS2 layer, SPPs (if generated by the optical illumination) can potentially couple strongly with the various excitonic species or act as a channel for hot carrier injection into the MoS2.…”
Section: 2: Experimental Details and Resultsmentioning
confidence: 99%